Tris[2-(1H-imidazol-2-yl)imidazol-1-ido]cobalt(III) - Ma, Qi (International Union of Crystallography, 2010)
In the title compound, [Co(C(6)H(5)N(4))(3)], the Co(III) atom adopts a distorted octahedral CoN(6) coordination geometry, arising from three N,N′-bidentate deprotonated 2,2′-biimidazole ligands. The dihedral angles between the five-membered rings of the ligands are 4.1 (2), 9.4 (2) and 10.5 (2)°. In the crystal, molecules are linked by N—H⋯N hydrogen bonds, generating a layered network lying in (11[Image: see text]).